(untitled) (African Journal of Science, Technology and Social Sciences, 2026)
The integration of information and communication technology (ICT) has become an essential element in educational transformation globally. Despite widespread recognition of its potential, the extent to which universities in Kenya incorporate technology into curriculum development remains underexplored. This study investigates the influence of technological factors on curriculum design at Meru University of Science and Technology (MUST). A correlational research design was employed, drawing data from chairpersons of academic departments and lecturers through questionnaires and document analysis. Findings reveal that technology significantly influences curriculum development, though challenges such as insufficient funding and limited training hinder effective implementation. The study concludes that embedding ICT into curricula enhances learning experiences and exposes students to vast knowledge beyond local contexts. Recommendations include increasing institutional investment in ICT, regular capacity-building workshops for lecturers, and policy-level prioritization of technological integration in higher education.